Digitizing Aceh's Historical Heritage: Exploring the Role of Technology in Cultural Preservation - Rahman, Aulia; Riyani, Mufti; Prasetyo, Okhaifi; Fransyaigu, Ronald; Asnawi, Asnawi; Shamadiyah, Nurasih (Universitas Negeri Medan, 2025)
Aceh is a region that has a rich historical and cultural heritage, which reflects its civilization and identity from time to time. However, the threat to the preservation of these historical relics is increasing over time, especially due to natural factors, urbanization, and social changes. Digitalization has emerged as a potential solution to address these challenges. The digitization of historical and cultural heritage offers a new way to preserve, access, and promote Aceh's cultural heritage more broadly. This research aims to explore the role of digital technology in the preservation of Aceh's cultural heritage, as well as its impact on local and global communities. This study uses a qualitative approach with a case study on the Aceh Historical Trail Map (acehhistorytrailmap.id). Data were collected through in-depth interviews with stakeholders, document analysis, and observation of platform usage. The analysis was conducted thematically to identify the benefits of digitalization, the technology used, and challenges in preserving cultural heritage. The study focuses on historical sites in East Aceh, such as Perlak and Idi, as the research locus. Through the analysis of case studies from the historical heritage digitization project in Aceh, this study examines the effectiveness of digital devices such as digital imaging, virtual tours, and online platforms in documenting and disseminating important elements of Acehnese culture, such as: artifacts and historical sites. The results of this research are expected to provide insight into effective strategies for cultural heritage preservation through technology, as well as the potential for collaboration between stakeholders in realizing sustainable digital transformation for the preservation of Aceh's historical heritage.